Historical overview of comparative education: George Bereday’s contributions - Madureira, Michele de Lourdes Alves; Brandão, Carlos da Fonseca; Laham, Stelamary Aparecida Despincieri (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
This article seeks to present an angle of the historical panorama drawn by Comparative Education, according to the documental bibliographic review carried out by the authors and to present the proposal of a comparative Bereday method. Initially, our methodological search turned to the different divisions into phases or periods proposed by classical authors. Soon after, we chose to bring the course of comparative education subdivided into decades and including how it also happened in the Brazilian scenario. In the following topic, our study focused on bringing the systematized methodology for comparative analysis proposed by George F. Z. Bereday, classic author of Comparative Education, whose legacy we can still recurrently observe in today's comparative studies.